Analysis of Methods of Control of CNC Machines in Cyber-Physical Production Systems - Yevsieiev, V.; Demska, N. (European Scientific Platform, 2021)
It is determined that the best option for the machine control system with CNC in the creation of cyber-physical production systems for Smart Manufacturing - are intelligent control systems that allow you to reflect physical processes in digital prostrate in real time, which is a key requirement in Ops 4.0 concepts.
Keywords: Computer Numeric Control; CNC machine